2020
DOI: 10.3390/medicina56120640
|View full text |Cite
|
Sign up to set email alerts
|

The Social Brain and Emotional Contagion: COVID-19 Effects

Abstract: Background and objectives: Coronavirus disease 2019 (COVID-19) is a highly contagious infectious disease, responsible for a global pandemic that began in January 2020. Human/COVID-19 interactions cause different outcomes ranging from minor health consequences to death. Since social interaction is the default mode by which individuals communicate with their surroundings, different modes of contagion can play a role in determining the long-term consequences for mental health and emotional well-being. We examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 71 publications
1
34
0
2
Order By: Relevance
“…Additionally, the subsequent pressure stemming from consecutive warnings, deadlines and targets on behalf of the higher positions in an organization may trigger a sense of unendurable stress that employees are prone to suffer causing in turn health issues and absenteeism at work (Bains & Chitrao, 2020;Wee et al, 2019). On top of that, stigma and discrimination by their peers and the possible emotional contagion of these in the workplace may affect individual self-efficacy causing emotional exhaustion, anxiety or even depressive symptoms that in the worst case-scenario may culminate in suicide (Barsade, 2002;Giorgi et al, 2020;Valenzano et al, 2020).…”
Section: Work Performance In the Current Scenariomentioning
confidence: 99%
“…Additionally, the subsequent pressure stemming from consecutive warnings, deadlines and targets on behalf of the higher positions in an organization may trigger a sense of unendurable stress that employees are prone to suffer causing in turn health issues and absenteeism at work (Bains & Chitrao, 2020;Wee et al, 2019). On top of that, stigma and discrimination by their peers and the possible emotional contagion of these in the workplace may affect individual self-efficacy causing emotional exhaustion, anxiety or even depressive symptoms that in the worst case-scenario may culminate in suicide (Barsade, 2002;Giorgi et al, 2020;Valenzano et al, 2020).…”
Section: Work Performance In the Current Scenariomentioning
confidence: 99%
“…We were unable to assess the type of social media content or social video games adolescents were engaging with; more research is needed to examine these nuances, how well they capture social connectedness, and links to mental health. Lastly, there is evidence to suggest that to exposure COVID-19 itself and/or the stress of COVID-19 may alter brain structures associated with mental health ( Valenzano et al, 2020 ). For example, one study found volumetric increases in brain regions commonly linked to internalizing disorders, in relation to a COVID-19-related lockdown ( Salomon et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of the COVID-19 crisis, there have been several studies examining the adverse psychological effects of state-imposed lockdowns [ 1 , 2 , 3 , 4 ]. There are also studies that examine the contribution of digital media and the internet to anxiety [ 5 , 6 ], emotional contagion [ 7 , 8 ], anxiety transmissions [ 9 , 10 ], and nocebo effects [ 11 , 12 ]. However, to our knowledge, there has been no study that analyzes how different political institutions and the state affect the development and extension of mass hysteria.…”
Section: Introductionmentioning
confidence: 99%